Numerical simulation of directional wave hydrodynamic force: A study of diffraction effects - Zuaini, Muhammad Nashriq Aiman (Universiti Teknologi PETRONAS, 2020)
Hydrodynamic forces on an offshore structure are normally defined by empirical models and clarified theories commonly the Morison’s equation. The best engineering method available to be used for computation of hydrodynamic forces is the Morison Equation which calculates the wave forces taking into account inertial forces (